The Value of Electricity Reliability: Evidence from Battery Adoption - David P. Brown; Lucija Muehlenbachs (CESifo GmbH, 2024)
To avoid electric-infrastructure-induced wildfires, millions of Californians had their power cut for hours to days at a time. We show that rooftop solar-plus-battery-storage systems increased in zip codes with the longest power outages. Rooftop solar panels alone will not help a household avert outages, but a solar-plus-battery-storage system will. Using this fact, we obtain a revealed-preference estimate of the willingness to pay for electricity reliability, the Value of Lost Load, a key parameter for electricity market design. Our estimate, with an average of 4,980/MWh, suggests California's wildfire-prevention outages resulted in losses from foregone consumption of 406 million to residential electricity consumers.
Keywords: Q40; Q54; Q58; 330; batteries; reliability; averting expenditures; power outages; Value of Lost Load